Report of the Work of the National Joint Committee for Spanish Relief, The British Committee for Refugees from Spain and The Basque Children's Committee (1939)
1939 038-0069-008 When the Foodships ceased, the Refugee ships began to sail. In May of this year the National Joint Committee chartered the S.S. SINAIA to sail as the first Spanish Refugee Ship to Mexico with 1,800 men, women and children on board. Families who had been separated were united to face this great adventure together. A representative of the British Committee for Spanish Refugees was in Mexico to greet them and to report on the conditions of their settlement. As a result of this effort, many other ships have since sailed to S. America. Emigration on a smaller scale is carried out by the British Committee's office at Perpignan—an average of 100 persons a week, of whom a large number are sent to join relatives in N. Africa. RELIEF IN FRANCE Conditions in the concentration camps were at first appalling, but gradually they have improved, and the British Committee has striven, in co-operation with the French authorities, to give the relief that was most needed day by day. Life in a concentration camp is one of such acute inaction that the mind as well as the body is in danger of permanent injury. The British Committee has therefore done everything possible to supply occupations for these unlucky people, giving them equipment for playing games, material for painting pictures, text-books for the study of languages. It has even been possible to set up in one of the camps an improvised university, library, and picture gallery. In meeting the need for food, clothes and medical supplies for the refugees, a happy state of co-operation between the voluntary organisations in France, the International Commission, the Spanish and French Relief Committees and the British Committee, resulted in a central organisation in Perpignan for the issuing of food and clothes for refugees in transit. Long queues of refugees waited patiently every day for the necessities of life as they passed through Perpignan to the camps, or in increasing numbers from Spain on their way to join their families in other parts of France. Often they had to wait months for the necessary papers to enable them to travel, and very often they had exhausted the small sums of money they brought with them on their flight. They were provided with food and clothes, and the British Committee supplied them with a railway ticket so that they might continue one stage further in their struggle to rebuild their lives. 4 292/946/38/69(VIII)